Building sustainable social and solidarity economies: Place-based and network-based strategies of alternative development organizations in India. Issue 1 (1st January 2018) - Kumbamu, Ashok
Abstract: This article critically examines and analyzes place-based as well as network-based strategies of alternative development organizations that claim to be building sustainable social and solidarity economies (SSE) in the political context of neoliberal globalization. While the Indian state and market forces are actively promoting the neoliberal agri-food system, alternative development organizations are working with farmers to build the SSE based on the principles of democracy, inclusiveness, reciprocity, cooperativism, and socioecological sustainability. Using a case study approach, this article analyzes how SSE initiatives are aiming to reclaim control over the local agri-food sector. Specifically, this article examines how community development organizations mobilize farmers based on the principles of agro-ecology and the politics of seed and food sovereignties. This article uses the Center for Sustainable Agriculture, an alternative community development organization in south India, as a case study.